2019
DOI: 10.1101/gr.244491.118
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of cardiomyocyte transcriptome and chromatin landscape demarcates key events of heart development

Abstract: Service Email Alerting click here. top right corner of the article or Receive free email alerts when new articles cite this article-sign up in the box at the http://genome.cshlp.org/subscriptions

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…These studies revealed highly dynamic chromatin states accompanying cardiac differentiation and development. Specifically, ATAC-seq is widely used on precious in vivo cardiac samples to identify genomic regions that are enriched for TF binding and functional enhancer elements ( Jia et al, 2018 ; Yuan et al, 2018 ; Pawlak et al, 2019 ; Racioppi et al, 2019 ). Recently, accessible chromatin profiling has also enabled the discovery of enhancers specific to cardiac subpopulations, such as pacemaker cells ( Galang et al, 2020 ; van Eif et al, 2020 ) and endocardial populations ( Boogerd et al, 2017 ).…”
Section: Unmasking Heart Enhancers With Comparative and Functional Gementioning
confidence: 99%
See 1 more Smart Citation
“…These studies revealed highly dynamic chromatin states accompanying cardiac differentiation and development. Specifically, ATAC-seq is widely used on precious in vivo cardiac samples to identify genomic regions that are enriched for TF binding and functional enhancer elements ( Jia et al, 2018 ; Yuan et al, 2018 ; Pawlak et al, 2019 ; Racioppi et al, 2019 ). Recently, accessible chromatin profiling has also enabled the discovery of enhancers specific to cardiac subpopulations, such as pacemaker cells ( Galang et al, 2020 ; van Eif et al, 2020 ) and endocardial populations ( Boogerd et al, 2017 ).…”
Section: Unmasking Heart Enhancers With Comparative and Functional Gementioning
confidence: 99%
“…Functional insights into cardiac enhancer regions continue to be made by studying TF occupancy and chromatin states upon the perturbation of cardiac TFs or signaling pathways in multiple organisms (e.g., Gata4, gata5 , Nkx2.5, Tbx5/tbx5, Tbx20, Hand2/hand2, Isl1, Foxf, Fgfr, Mek, and Ras ) ( He et al, 2014 ; Luna-Zurita et al, 2016 ; Boogerd et al, 2017 ; Jia et al, 2018 ; Pawlak et al, 2019 ; Racioppi et al, 2019 ), as well as in a human congenital heart disease (CHD) model (cardiomyocytes with a disease-associated missense mutation of GATA4 ) ( Ang et al, 2016 ). These studies reveal the master regulatory roles of cardiac TFs at the chromatin level.…”
Section: Unmasking Heart Enhancers With Comparative and Functional Gementioning
confidence: 99%
“…In several other studies, comparative analyses were performed between organisms other than zebrafish to detect evolutionarily conserved regions (ECRs) in the heart. The zebrafish system allows live enhancer assay, and conservation of enhancer function between zebrafish and mammals has been demonstrated [ 58 , 62 , 64 , 101 , 115 ]. Due to these features, many candidate enhancers identified in the mammalian system were validated in the zebrafish system [ 57 , 63 , 108 , 116 , 117 ].…”
Section: The Quest For Enhancers Involved In Heart Development and Functionmentioning
confidence: 99%
“…Recently, we capitalized on the power of genomics analyses and the zebrafish model system to capture the dynamics of regulatory landscape and gene regulatory network throughout the progression of zebrafish heart morphogenesis in vivo [ 58 ]. We combined transcriptome profiling (RNA-seq) with an assay for chromatin accessibility (ATAC-seq) on isolated CMs from wild-type zebrafish heart at key stages of heart morphogenesis corresponding to linear heart tube formation, chamber formation/differentiation, and heart maturation.…”
Section: The Quest For Enhancers Involved In Heart Development and Functionmentioning
confidence: 99%
See 1 more Smart Citation